The effects of reducing bird predation on canopy arthropods of marri (Eucalyptus calophylla) saplings on the Swan Coastal Plain, Western Australia - Evelegh, N.; Majer, Jonathan; Recher, H. (2001)
The effect of bird predation on canopy arthropods inhabiting Marri (Eucalyptus calophylla) saplings was examined in Banksia woodland on the Swan Coastal Plain of Western Australia. Twenty pairs of saplings were selected and one of each pair was enclosed in bird-proof mesh to exclude foraging birds. Saplings were sampled in April 1998, prior to bird exclusion, and in August 1997, October 1997 and May 1998 after exclusion. Abundance, species richness and size of some arthropods increased on meshed saplings in certain months following bird exclusion. Spiders (Araneae) were most different between meshed and open saplings, with their abundance increasing on the saplings from which birds were excluded and remaining significantly more abundant after one year. The abundance of larger arthropods (in particular, spiders) increased and smaller animals decreased following bird exclusion, suggesting an interaction with birds on spiders as prey, and between spiders and their prey.Additional evidence of an effect of bird predation on the arthropod fauna was found in the amount of arthropod-related damage to leaves on meshed and open saplings. Damage to leaves, recorded over an 8-week period in spring, on meshed saplings was 21% of total leaf area, compared with 6% on open saplings. These differences indicate that damage to canopy foliage is reduced by bird predation of herbivorous arthropods, and are consistent with trends in arthropod abundances between open and meshed saplings. We conclude that predation by birds affects the composition and size structure of canopy arthropod communities on eucalypts, and there is merit in initiating longer and more extensive studies.